Sustainable Palm Oil Plantation Management Model: Case Study Of Palm Palm Waste Utilization - Harefa, Taslim; Lubis, Yusniar; Martial, Tri (Universitas Muhammadiyah Jember, 2024)
This study aimed to determine whether sustainable palm oil plantation processing through the utilization of palm oil waste itself is very effective. This is based on the many errors in processing palm oil land that result in land damage, such as excessive use of chemical fertilizers. Data collection in this study used qualitative methods. Data collection was carried out using observation, interview, and documentation techniques. The study was conducted at PT. Padasa Enam Utama and PT. Inti Kamparindo Sejahtera. The study's findings indicate that using liquid palm oil waste and palm fronds is also very efficient. Palm oil waste will become an organic material that does not damage the soil. On the other hand, palm oil waste will also be helpful in fertilizing oil palm plants. So, using palm oil fronds as an alternative to fertilization is very good. This is because palm oil fronds will not damage the nutrients in the soil. Therefore, palm oil fronds and liquid waste can be an option in sustainable palm oil processing